Macrophages impede CD8 T cells from reaching tumor cells and limit the efficacy of anti–PD-1 treatment - Peranzoni, Elisa (Proc Natl Acad Sci U S A, 2018)
In a large proportion of cancer patients, CD8 T cells are excluded from the vicinity of cancer cells. The inability of CD8 T cells to reach tumor cells is considered an important mechanism of resistance to cancer immunotherapy. We show that, in human lung squamous-cell carcinomas, exclusion of CD8 T cells from tumor islets is correlated with a poor clinical outcome and with a low lymphocyte motility, as assessed by dynamic imaging on fresh tumor slices. In the tumor stroma, macrophages mediate lymphocyte trapping by forming long-lasting interactions with CD8 T cells. Using a mouse tumor model with well-defined stromal and tumor cell areas, macrophages were depleted with PLX3397, an inhibitor of colony-stimulating factor-1 receptor (CSF-1R). Our results reveal that a CSF-1R blockade enhances CD8 T cell migration and infiltration into tumor islets. Although this treatment alone has minor effects on tumor growth, its combination with anti–PD-1 therapy further increases the accumulation of CD8 T cells in close contact with malignant cells and delays tumor progression. These data suggest that the reduction of macrophage-mediated T cell exclusion increases tumor surveillance by CD8 T cells and renders tumors more responsive to anti–PD-1 treatment.